THE CRITIQUE AND ALTERNATIVE IDEOLOGY TOWARD THE EASTERN ECONOMIC CORRIDOR (EEC) DEVELOPMENT - Phattanapol, Manas; Praditsil, Chaiyon; Sansanoh, Chamlong (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The objectives of this research were to 1) critique the ideologies of the Eastern Economic Corridor (EEC) development, and propose alternative ideologies for building sustainable development in the Eastern Region. The research methodology was based on a qualitative and interdisciplinary approach and critical discourse analysis method. Data collection was derived from document inquiries and in–depth interviews. The research findings were as follows: 1) The critique of the ideologies regarding the EEC development found that neoliberalism, as an external ideology, played a limited role in the EEC development process; on the other hand, applying a neoliberal critique to the ideologies showed that the project was primarily focused on capitalist development. This involved legitimizing capitalism–based reproduction through capital accumulation and economic growth, which often benefited a minority group of elites within a quadruple system. Consequently, this approach contributed to economic inequality, with negative impacts and disadvantages of capitalism affecting a much larger number of people in the society; and 2) Recommendations for alternative ideologies to support sustainable development in the Eastern Region suggest that the ideologies and developmental strategies benefiting public and local communities include social–ecological communitarianism and developmental strategies emphasizing community participation, ecological justice, equality of outcomes, and community empowerment, all of which could serve as guidelines for the EEC development.